Proyecto de desarrollo sostenible para comunidad a través de la gestión participativa en la parroquia Pifo - Iza Carrión, Lorena Isabel (2007)
Establish a model and operational structure of micro and small agricultural producers to ensure sustainable development and participatory management in the Pifo parish.